The Survey of Family /Community involvement in Schools' Health Planning and Policymaking - Rahim Khodayari-Zarnaq; Leila Torkzadeh; Somayeh Heydari; Hojjat Rahmani; Nazanin Mir; Habib Jalilian (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Schools play a crucial role in developing a healthy lifestyle and community participation, especially family participation, which is essential to schools' success in achieving this role. This study aimed to examine the family/community involvement in schools' health planning and policymaking from the principal and lead health education teacher in Tabriz, Iran. Methods: This cross-sectional study was conducted in 2016. The statistical population included all school principals and lead health education teachers in Tabriz, Iran. A total of 93 schools were included. A systematic random sampling method was used for data collection. Data were collected using the School Health Profiles. The content validity of the profile was revised by an expert involved in school health. The questionnaire's reliability was calculated by internal consistency and Cronbach's alpha coefficient. Data were analyzed using SPSS22. Mann-Whitney and Kruskal-Wallis tests were applied to examine the difference between the type of school (in terms of ownership, gender, and grade) and the school's percentage that attracts family/community participation. Results: According to the results, only 53.80 % of schools actively collaborated with students' families in developing and implementing policies and programs related to health school. The majority of schools (83.30 %) provided parents with educational content on nutrition and healthy eating, while only 40 % of them provided parents with educational content on HIV prevention, STD prevention, teen pregnancy prevention, and asthma. Moreover, more than 50 % of schools worked with other staff groups about health education activities. In most schools (73.30 %), health education teachers worked with physical education staff, while in 53.30 % of them, health education teachers worked with nutrition or service staff on health education activities. Conclusion: Given a low percentage of school and family/community partnerships in school health-promotion programs in most dimensions, comprehensive and integrative planning must be implemented to create engagement and collaboration with other community sectors.